2009
DOI: 10.1111/j.1439-0418.2008.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungi associated with a natural epizootic in Fiorinia externa Ferris (Hemiptera: Diaspididae) populations

Abstract: Stands of eastern hemlock [(Tsuga canadensis (L.) Carrière] in the northeastern United States are in decline, in part from the attack of elongate hemlock scale, Fiorinia externa Ferris (Hemiptera: Diaspididae). From 2001 to the present, a natural epizootic has been observed in populations of F. externa. Initially discovered at the Mianus River Gorge Preserve in Bedford, New York, the epizootic has also been detected in Pennsylvania, New Jersey and Connecticut. Understanding and assessing the identity of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…and others have been recovered from infected pear thrips [ 9 , 10 ]. Other fungal isolates have been found to be associated with elongate hemlock scale and lecanium scale [ 11 , 12 , 13 , 14 ]. These entomopathogenic agents offer an opportunity for biological regulation of exotic invasive species, especially when the fungal pathogens are found associated with epizootic processes, where a rapid decline of the pest population is occurring [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…and others have been recovered from infected pear thrips [ 9 , 10 ]. Other fungal isolates have been found to be associated with elongate hemlock scale and lecanium scale [ 11 , 12 , 13 , 14 ]. These entomopathogenic agents offer an opportunity for biological regulation of exotic invasive species, especially when the fungal pathogens are found associated with epizootic processes, where a rapid decline of the pest population is occurring [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited published information about Colletotrichum species infecting insects (Marcelino et al, 2008(Marcelino et al, , 2009a(Marcelino et al, , 2009b and scarce knowledge concerning the temporal dynamics of citrus orthezia/Colletotrichum pathogen populations. In this study, we confirmed the identity of an endemic insect pathogen (identified here as C. nymphaeae) infecting the scale P. praelonga in citrus groves under different regimes of chemical pesticide use.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Colletotrichum acutatum var. fioriniae was noted to cause epizootics on the elongate hemlock scale, Fiorinia externa (Hemiptera: Diaspididae), in the United States (Marcelino et al, 2008(Marcelino et al, , 2009a(Marcelino et al, , 2009b. To date, it appears that these are the two exceptional cases in which Colletotrichum was found associated with insects.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…and Unaspis citri (Comstock). On the other hand, Marcelino et al, (2009) observed a natural epizootic in populations of diaspidid Fiorinia externa. A total of 121 fungal isolates of the entomopathogenic species: Colletotrichum sp., L. muscarium, Beauveria bassiana, Metarhizium microspora, and Myriangium sp.…”
Section: Introductionmentioning
confidence: 99%